Mechanical Calculation of Flexible Wires of Spans with Different Tensioning Insulator Strings - Yu. V. Bladyko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
In design activities, technical solutions are practiced, which provide for the use of different tension strings of insulators in a single span. The present paper considers the calculation of the sag and load factors for a span with two different tensioning insulator strings that are of identical suspension heights. The system of “the first tension insulators string – the wire – the second tension insulators string” was described by the equations of a parabola. A relationship has been established between the sag increase factor and the coefficients that take into account the presence of tensioning insulators strings. The resulting compact formula for sag increase is generally suitable for any combination of strings in a span. The coincidence of the calculation is shown for particular cases known from the literature. The formula for calculating the load factor for the equation of state was derived, taking into account the presence of different strings in the span. The reliability of the formula has been proved by the coincidence of results for particular cases of the arrangement of strings. The obtained expressions can be used both for vertical (weight and ice) loads and for horizontal (wind) ones. In the case of loads in two planes, the equation of state must take into account all the components when calculating the resulting reduced load on the wire along the inclined plane. Calculations were performed for different lengths of spans of switchgear with different wires and strings of insulators. A span with one and two tensioning strings of insulators, with the same suspension heights, in the absence of wind and ice is considered. The curves of the sagging wires to different strings have been plotted. It is demonstrated that when calculating sags and tensions, the difference between strings must not be neglected.